A magnificent enzyme superfamily: carbonic anhydrases, their purification and characterization. (2nd September 2016) - Ozensoy Guler, Ozen; Capasso, Clemente; Supuran, Claudiu T.
Abstract: In this paper, we reviewed the purification and characterization methods of the α-carbonic anhydrase (CA, EC 4.2.1.1) class. Six genetic families (α-, β-, γ-, δ-, ζ- and η-CAs) all know to date, all encoding such enzymes in organisms widely distributed over the phylogenetic tree. Starting from the manuscripts published in the 1930s on the isolation and purification of α-CAs from blood and other tissues, and ending with the recent discovery of the last genetic family in protozoa, the η-CAs, considered for long time an α-CA, we present historically the numerous and different procedures which were employed for obtaining these catalysts in pure form. α-CAs possess important application in medicine (as many human α-CA isoforms are drug targets) as well as biotechnological processes, in which the enzymes are ultimately used for CO2 capture in order to mitigate the global warming effects due to greenhouse gases. Recently, it was discovered an involvement of CAs in cancerogenesis as well as infection caused by pathogenic agents such as bacteria, fungi and protozoa. Inhibition studies of CAs identified in the genome of the aforementioned organisms might lead to the discovery of innovative drugs with a novel mechanism of action.